Restorasi Pengembangan Tepi Sungai Krueng Aceh - Muhammad - Ardy; Irin Caisarina; Hilda Mufiaty (Jurnal RAUT, 2023)
The Krueng Aceh River is a river that has a strategic function in supporting the activities of the people of the city of Banda Aceh which has the potential for beauty so that it can be developed to realize the city of Banda Aceh as a waterfront city. The riverside area as a public open space in the form of a park can be used as a means of relaxation for the community. The park on the banks of the Krueng Aceh River, which is located in the Baiturrahman sub-district, Banda Aceh City, has seen arrangements carried out by the government. This park is included in the waterfront city area which is a tourist area and public space in Qanun Number 4 of 2009 concerning the Banda Aceh City Regional Spatial Planning Plan (RTRW) for Banda Aceh City for 2009-2029. However, based on observations in the field, it can be seen that there are several physical problems in the form of damaged infrastructure and inadequate spatial planning. Based on the above, this research aims to identify the existing condition of the park and improve the quality of public open space to maximize the function of space in the park along the Krueng River, Aceh. This type of research is qualitative with data collection carried out using the snowball sampling method. The research results show that the waterfront element in this park already exists but needs to be improved and to support the use of the park as a public open space it needs to be reconsidered regarding aspects of the quality of public space in the Krueng Aceh area.Keywords: Waterfront City, Taman Tepi Sungai, Ruang Terbuka Publik, Kota Banda Aceh.